‘TABULAMPOT’ TEKNIK BUDIDAYA USAHATANI JAMBU AIR MADU DELI HIJAU - Nina Maksimiliana Ginting (Musamus University, 2019)
This study aims to determine the technique of guava cultivation of Deli Green Honey, the costs incurred by water guava farmers of Deli Green Honey variety, income generated by water guava farmers of Honey Deli Green variety, and the feasibility issued by water guava farmers of Honey Deli Green variety. This research was conducted in Payaroba Village, Binjai Barat District, Binjai City which was conducted purposively. The sampling method is by using the census method. The analytical method used is descriptive analysis method, cost and income calculation method, and feasibility analysis method (R / C ratio. Based on the results of the study concluded 1) Guava farming stages green deli honey water starts from planting, watering, fertilizing, spraying, pruning , wrapping fruit and harvesting. 2) The average total cost of green deli honey guava farming costs Rp. 62,104,066 / year 3) The average income of green deli honey water farming is Rp. 49,503,566 / year. 4) guava farming green deli honey water in the research area is worth the effort with the R / C ratio of 1.79> 1, Keywords: tabulampot, MDH guava water, income, R / C ratio